Volatile chemical emission as a weapon of rearguard action: a game-theoretic model of contest behavior - Mesterton-Gibbons, Mike; Dai, Yao; Goubault, Marlene; Hardy, Ian C.W. (Springer, 2017)
We use a game-theoretic model to explore whether volatile chemical (spiroacetal) emissions can serve as a weapon of rearguard action. Our basic model explores whether such emissions serve as a means of temporary withdrawal, preventing the winner of the current round of a contest from translating its victory into permanent possession of a contested resource. A variant of this model explores an alternative possibility, namely, that such emissions serve as a means of permanent retreat, attempting to prevent a winner from inflicting costs on a fleeing loser. Our results confirm that the underlying logic of either interpretation of weapons of rearguard action is sound; however, empirical observations on parasitoid wasp contests suggest that the more likely function of chemical weapons is to serve as a means of temporary withdrawal. While our work is centered around the particular biology of contest behavior in parasitoid wasps, it also provides the first contest model to explicitly consider self-inflicted damage costs, and thus responds to a recent call by empiricists for theory in this area.